Solution of System of Fractional Differential Equations Using Variational Iteration Method - Pandey, Shweta; Dixit, Sandeep (International Journal of Computer Sciences and Engineering, 2025)
In this paper, an approximate method to solve system of fractional differential equations analytically, fractional heat-like two-dimensional equation and stiff system of differential equations of nonlinear kind is obtained using variational iteration method (VIM). The results demonstrate that our approach is straightforward, effective and very simple. The numerical findings for different cases of problems are presented graphically. The outcomes reveal that the VIM is convenient, stable and performs extremely good in terms of simplicity and efficiency